Pemanfaatan Blockchain untuk Meningkatkan Keamanan Siber dalam Pembayaran Lintas Batas di Industri Fintech - Uky Zaza Agustiana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The cross – border fintech payment industry faces many cybersecurity issues, including the possibility of data theft, fraud and low efficiency due to reliance on conventional intermediaries. Based on decentralized and cryptgrahpic system, blockchain technology can improve the security and efficiency of cross – border payments. The purpose of this study is to see how the implementation of blockchain affects the transparency, speed and cost of transactions. Using literature studies and case analysis, it was found that blockhain technology can reduce the risk of fraud by making institutions transparent and immutable. In addition, it allows for automated payments through smart contracats, scalability, regulation and technology adoption are some of the challenges that still hinder its implementation. The results of the study show that blockchain is an innovation strategy that has the potential to transform payments across the fintech sector, but it requires synergy between technology, policy and industry players for optimal implementation.